Indigenous leafy vegetables of Eastern Africa — A source of extraordinary secondary plant metabolites. (October 2017) - Neugart, Susanne; Baldermann, Susanne; Ngwene, Benard; Wesonga, John; Schreiner, Monika
Abstract: Indigenous African leafy vegetables vary enormously in their secondary plant metabolites whereat genus and the species have a great impact. In African nightshade ( Solanum scabrum ), spiderplant ( Cleome gynandra ), amaranth ( Amaranthus cruentus ), cowpea ( Vigna unguiculata ), Ethiopian kale ( Brassica carinata ) and common kale ( Brassica oleracea ) the specific secondary metabolite profile was elucidated and gained detailed data about carotenoids, chlorophylls, glucosinolates and phenolic compounds all having an appropriate contribution to health beneficial properties of indigenous African leafy vegetables. Exemplarily, various quercetin glycosides such as quercetin-3-rutinoside occur in high concentrations in African nightshade, spiderplant, and amaranth between ~ 1400–3300 μg/g DW. Additionally the extraordinary hydroxycinnamic acid derivatives such as glucaric isomers and isocitric acid isomers are found especially in amaranth (up to ~ 1250 μg/g DW) and spiderplant (up to 120 μg/g DW). Carotenoids concentrations are high in amaranth (up to101.7 μg/g DW) and spiderplants (up to 64.7 μg/g DW) showing high concentrations of β-carotene, the pro-vitamin A. In contrast to the ubiquitous occurring phenolics and carotenoids, glucosinolates are only present in the Brassicales species Ethiopian kale, common kale and spiderplant characterized by diverse glucosinolate profiles. Generally, the consumption of a variety of these indigenous African leafy vegetables can be recommended to contribute to different benefits such as antioxidant activity, increase pro-vitamin A and anticancerogenic compounds in a healthy diet. Graphical abstract: Highlights: Secondary plant metabolites highly vary depending on plant species. High concentration of quercetin glycosides in four of five African species. Extraordinary hydroxycinnamic acid derivatives occur in amaranth and spiderplant. High concentrations of β-carotene, the pro-vitamin A, in amaranth and spiderplant Diverse glucosinolate profiles in Brassicales species spiderplant and kale